Gene Targeting in Mouse Embryonic Stem Cells - Tessarollo, Lino (Methods Mol Biol, 2009)
The scientific value of a mouse model with a targeted mutation depends greatly upon how carefully the mutation has been engineered. Until recently, our ability to alter the mouse genome has been limited by both the lack of technologies to conditionally target a locus and by conventional cloning. The “cre/loxP” and “recombineering” technologies have overcome some of these limitations and have greatly enhanced our ability to manipulate the mouse genome in a sophisticated way. However, there are still some practical aspects that need to be considered to successfully target a specific genetic locus. Here, we describe the process to engineer a targeted mutation to generate a mouse model. We include a tutorial using the publicly available informatic tools that can be downloaded for processing the genetic information needed to generate a targeting vector.